2019
DOI: 10.1055/a-0926-3790
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics in the Diagnosis of Pheochromocytoma and Paraganglioma

Abstract: Metabolomics refers to the detection and measurement of small molecules (metabolites) within biological systems, and is therefore a powerful tool for identifying dysfunctional cellular physiologies. For pheochromocytomas and paragangliomas (PPGLs), metabolomics has the potential to become a routine addition to histology and genomics for precise diagnostic evaluation. Initial metabolomic studies of ex vivo tumors confirmed, as expected, succinate accumulation in PPGLs associated with pathogenic variants in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…While SDHB‐IHC assesses presence of the protein, LC–MS/MS‐based metabolite profiling provides information about functionality of the succinate complex through measurements of precursor and product metabolites. There is also the added benefit of measuring a panel of metabolites to identify impaired function of other enzymes, such as fumarate hydratase and isocitrate dehydrogenase [12,22]. Metabolite measurements also address some of the limitations of SDHB‐IHC: in particular, there is no subjective bias of interpretation and there is always a numerical result rather than inconclusive interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…While SDHB‐IHC assesses presence of the protein, LC–MS/MS‐based metabolite profiling provides information about functionality of the succinate complex through measurements of precursor and product metabolites. There is also the added benefit of measuring a panel of metabolites to identify impaired function of other enzymes, such as fumarate hydratase and isocitrate dehydrogenase [12,22]. Metabolite measurements also address some of the limitations of SDHB‐IHC: in particular, there is no subjective bias of interpretation and there is always a numerical result rather than inconclusive interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…PCPGs manifest a strong hypoxic-like signaling, abnormal mitochondrial morphology as well as DNA hypermethylation, which is increasingly recognized in SDHx-mutated PCPG [ 116 ]. Besides, early metabolomic studies showed that SDHx-associated tumors possessed high levels of methionine that might be consistent with DNA hypermethylation [ 117 ]. It is likely that NNMT under-expression helps PCPG cells to sustain a high SAM level, leading to the maintenance of DNA hypermethylation and catecholamines formation.…”
Section: Nnmt Expression In Different Tumorsmentioning
confidence: 99%
“…The metabolome is defined as the set of small molecules present in the cell and in its proximal environment, essential to its functions and maintenance, which reflect the result of biochemical reactions and determine its phenotype. It is influenced by genetic, environmental, and epigenetic factors, which may correspond to an indirect way of diagnosing cellular dysfunction [8]. Metabolome deregulation in PPGL results from the activation of hypoxia signaling pathways.…”
Section: Metabolomementioning
confidence: 99%
“…The metabolic changes identified in PPGL reflect the activation of hypoxia pathways, with similarity in PPGL with different genetic origins. The assessment of the metabolome characteristics has allowed the validation of enzymatic defects in some PPGL, such as the role of fumarate hydratase (FH), isocitrate dehydrogenase (IDH), malate dehydrogenase (MDH2), and aspartate transaminase (GOT2) [8]. RNA-based mechanisms were also found to have a profound role in physiological processes such as immunity, metabolism, cell apoptosis, differentiation, proliferation, and control of angiogenesis [9].…”
Section: Introductionmentioning
confidence: 99%